Cybersecurity for the Protection of IOT Devices in the Industrial Sector - Oliva Olazábal, Alex Alberto; Llanos, Clariza; Alarcón, Felipe; León-Velarde, César (LACCEI, 2024)
With every passing day, new forms of attacks on IoT devices appear in the industrial sector. This research aims to identify common vulnerabilities, develop protection strategies, and establish guidelines to mitigate risks of cyber attacks. The PICO and PRISMA method was used to evaluate the review. Based on the established inclusion and exclusion criteria, 30 free access articles were selected from the Scopus, IEEE database corresponding to a systematic review of the literature. The analyzed results identified multiple vulnerabilities in industrial IoT devices, such as authentication failures, lack of data encryption, and firmware vulnerabilities. Security solutions were implemented, including firmware updates, implementation of robust encryption protocols, and staff training in cybersecurity best practices. The conclusions were reached: Cybersecurity in industrial IoT devices is crucial to prevent possible cyberattacks that could affect the production and integrity of the systems. Implementing preventive and corrective measures is essential to protect industrial infrastructure against constantly evolving cyber threats. It is also important to highlight the need for continued collaboration between manufacturers, operators and cybersecurity experts to ensure effective protection of IoT devices in the industrial sector